Peningkatan Keterampilan Sosial Siswa Melalui Model Make A Match Di Kelas Tinggi - Putri Anggita Sari; Iis Nurasiah; Arsyi Rizqia Amalia (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study is designed to describe the planning and implementation of a match learning model, and describes improvement in social skills through the Make a Match Learning model for students in high school elementary school. The research method used in the research is the Classroom Action Research (CAR) with each cycle consisting of planning, action, observation, and reflection. The fifth grade students were from Kebonjati Elementary School. Consisting of 21 male students and 21 female students. Data collection techniques in this study used observation, field notes, and registration. Based on the data obtained from the results of the study, the teacher obtained an average value of 71 with an average value of 68 with a fairly active category in cycle 1. While in cycle 2 the average value of 73 in the active category. Fulfilling the social training indicator values ​​reached an average of 76 in the good category. The action of learning continues with the 2nd cycle. In cycle 2, the indicator of students' skills reaches an average of 82 with a very good category. From these results, we have drawn conclusions from successful research because the value of the skills is very good received from students. In order to improve social skills of students in SDN Kebonjati.